Male genital tract versus blood HIV-1 compartmentalization and selection: the first step of the transmission bottleneck? - Kariuki, Samuel Mundia (Division of Immunology, 2020)
Introduction Sexual transmission of HIV-1 accounts for more than 80% of all the transmissions globally. After transmission, approximately 80% of the newly disseminated infections can be traced to a single variant, which comes from the minor HIV-1 population within the transmitting donor. This has led to the widely accepted idea of an HIV-1 transmission bottleneck. The nature of this bottleneck is not fully understood. Many studies working on understanding the nature of the transmitted virus have reported discordant traits of transmitted/founder viruses compared to viral isolates from chronically infected individuals. Such studies therefore lacked analysis of the intermediate step between these two populations: HIV-1 from the genital tract of the donors: where viruses are on their way to transmission to a new recipient. Importantly, numerous prior studies have shown that there is compartmentalization of HIV-1 populations between the general circulation and the genital tract, raising the possibility that the genital tract is an important selective environment. Collectively, prior studies of genital tract compartmentalization in males detected compartmentalization in about half of the donors studied, although by using techniques with limited depth of sampling than that employed in our study. The virus that establishes disseminated infection in a new recipient is selected. However, the extent to which this selection occurs before, during or after crossing the mucosal surfaces of the recipient is less clear – the period during which transmission selection could extend far back to the donor, and the donor’s genital tract. In other words, it is not clear as to what extent the transmission bottleneck occurs during compartmentalization of viral populations in the genital tract tissues. The design of an effective vaccine and other intervention strategies will rely upon the understanding the nature of the transmitted virus as this is the virus that must be targeted. This thesis Compartmentalization of minor variants cannot be tracked by techniques previously used to describe compartmentalization between the genital tract and the blood circulation. We therefore used deep sequencing-based techniques to further understand compartmentalization of viral populations between blood and the male genital tract. In addition, we tested the sensitivity of variants to a range of entry and other inhibitors in order to explore possible changes in function that may arise when viral variants grow in the shifted selective milieu of the genital tract. We further hypothesized that this change of selective milieu as HIV-1 moves from blood into the genital tract may lead to viral variants in semen that are sensitive to autologous neutralization because such sensitive variants may be able to grow in the genital tract, which is presumably partially or completely shielded from antibodies. Because the viral populations in semen comes from a site that may be relatively protected from antibodies, they may be permitted to evolve differently in the relative absence of antibody pressure. It is possible that evolution of the virus within the genital tract is a significant part of the change the virus undergoes on its way to establishment of a new disseminated infection in the new recipient. We considered this possibility because even some small molecules like those of some antiretroviral drugs do not penetrate the genital tract effectively under some circumstances, raising the possibility that antibodies might not always penetrate in all areas of the genital tract. This thesis had three objectives: 1. To evaluate HIV-1 compartmentalization in blood and the male genital tract using next generation sequencing to understand the nature of viral populations in these anatomical sites in greater detail. 2. To identify the differences in sensitivity of blood and semen variants to entry inhibitors to obtain information about differences in function between HIV-1 populations in blood vs the male genital tract. 3. To compare neutralization sensitivities of viral variants compartmentalized in blood and semen by testing their sensitivity to neutralization by autologous antibodies. As a control, we measured sensitivity to a pool of clade-matched heterologous sera to determine if any observed difference was due to global changes in neutralization sensitivity.